Generating multiple resilience dividends from managing unnatural disasters in Asia opportunities for measurement and policy. - Mechler, Reinhard ([Manila] Asian Development Bank, 2019)
Despite solid evidence of the benefits of reducing disaster risk, it remains difficult to motivate investment in disaster risk reduction. International debate emphasizes investments that generate multiple dividends through reducing loss of life and livelihoods, unlocking development potential, and creating development cobenefits. The authors report multiple dividend evidence and emphasize that decision support tools, including resilience capacity measurement approaches, can encourage participatory decision making with those at risk and identify interactions between development and disaster risk.
Keywords: Natural disasters -- Risk assessment -- Asia; Natural disasters -- Economic aspects -- Asia; Electronic books